ROOTING OF KIWIFRUIT (Actinidia deliciosa Lang et Ferguson cv. Bruno)CUTTINGS IN THE FOUR SEASONS OF THE YEAR - PAES, Elisângela da Graça Boeno; ZUFFELLATO-RIBAS, Katia Christina; BIASI, Luiz Antonio; KOEHLER, Henrique Soares (Scientia Agraria, 2003)
Propagation of the kiwifruit (Actinidia deliciosa A. Chevallier (C. F. Lang et A. R. Ferguson)) usually is done through grafting of crown over rootstocks. Aiming to decrease time for formation of rootstocks followed by grafting, the present seeks an alternative for the species propagation using direct cutting from crown as a technique for faster speed and efficiency. Different concentrations of synthetic auxins, indolebutyric acid (IBA) and naphtaleneacetic acid (NAA), in solution and powder, were applied in the kiwifruit stem cuttings of Bruno cultivar. They were collected during the four-year seasons (autumn/2001, winter/2001, spring/2001 and summer/ 2002) at Porto Amazonas, PR. The stem cuttings were prepared with approximately 12 cm length being their bases immersed for 10 seconds in the solutions and in powder combinations as follows: T1: distilled water; T2: 2500 mg.L-1 IBA (solution); T3: 5000 mg.L-1 IBA (solution); T4: 2500 mg.L-1 NAA (solution); T5: 5000 mg.L-1 NAA (solution); T6: inert powder; T7: 2500 mgKg-1 IBA (powder); T8: 5000 mg.Kg-1 IBA (powder); T9: 2500 mg.Kg-1 NAA (powder); T10: 5000 mg.Kg-1 NAA (powder), then they were planted in plastic containers using vermiculite as growing media and kept in greenhouse with intermittent mist. After 70 days the following variables were observed: rooted stem cutting percentage; callus stem cutting percentage; alive stem cutting and dead stem cutting percentage. Through this work it was possible to conclude that there is heterogeneity of the rooting potential in the four seasons of the year; the largest rooting average was obtained with 5000 mg.Kg-1 NAA in powder in the winter.